Application of AHP Method in Determining Priority Work Accident Areas at CV Pesona Mebelindo - Laila Fitriana; Choirunnisa Fajriati (Journal of Mathematics and Mathematics Education, 2024)
This research aims to determine the priority order of work accident areas in the furniture business at CV Pesona Mebelindo. One of the urgencies of this research is that the number of work accidents in Indonesia is still relatively high, so prevention efforts are needed to minimize the number of work accidents. The method used in this research is Analytical Hierarchy Process (AHP). In this method, there are three important parts, namely goals, criteria and alternatives. The aim of this research is to determine priority areas for work accidents. The criteria in this research include workers, environment and equipment. Meanwhile, alternatives in this research include the raw goods room, material room, sanding room, finishing, packing and stuffing. The data collection process was obtained from questionnaires filled out by workers at CV Pesona Mebelindo which were processed into a pairwise comparison matrix, matrix normalization, determining importance weights, and calculating consistency ratios with the condition that the CR value had to be below 10%. By using the Analytical Hierarchy Process (AHP) method, the priority order of work accident areas at CV Pesona Mebelindo was obtained, namely the sanding, finishing, packing, stuffing, materials room and raw goods room